Nonlinear Vibration of Microbeams Based on The Elastics Foundation Using High-Order Energy Balance Method and Global Error Minimization Method - V. Hieu, D (International Journal of Engineering and Technology, 2018)
In this paper, nonlinear vibration of microbeams based on the nonlinear  elastic  foundation  is  investigated. The  equation  of motion of microbeams based on three-layered nonlinear elastic medium (shear, linear and nonlinear layers) is described by the partial differential equation by using the modified couple stress theory.  The equation of motion of microbeams is transformed  into the ordinary differential equation by using Galerkin method. The high-order Energy Balance  method and the high-order Global Error Minimization method are  used  to  get  the  frequency –  amplitude relationships  for  the  nonlinear  vibration  of  microbeams  with pinned-pinned  and  clamped-clamped  end  conditions. Comparisons between the present solutions and the privious solutions  show  the  accuracy  of  the  obtained  results.